Tingkat Partisipasi Anggota Kelompok Tani di Kampung Sayur Bausasran Kecamatan Danurejan Kota Yogyakarta: Sita Diani Putri - Sita Diani Putri (Sumber Penyuluhan Pertanian Indonesia, 2023)
This research aimed to (1) analyze participation rate of farmer group members in Kampung Sayur Bausasran, and (2) analyze the influence of factors such as education level, main ocupation, vegetable farming experience, extension officer performance and Government facilitation towards the participation of farmers group members in Kampung Sayur Bausasran. Research implementation method used was quantitative method with descriptive approach. Method of determining the research location used was purposive method namely in Kampung Sayur Bausasran, Danurejan, Yogyakarta. Sample taking method used was proportional cluster random sampling method. Data type used in this research are primary and secondary data. Data collecting method were by taking interview, documentation and observation. To analyze the influence of factors such as education level, main livelihood, vegetable farming experience, extension officer performance and Government facilitation towards farmers group member, multiple linear regression analysis was used. This research result showed that (1) participation rate of famer group member in Kampung Sayur Bausasran was high, and (2) factors such as education level, main ocupation, vegetable farming experience, extension officer performance, and Government facilitation significantly affected the participation rate of famer group members in Kampung Sayur Bausasran.